Sulfoxides as Response Elements for Fluorescent Chemosensors: Does It Work? (Journal of Atomic and Molecular Sciences, 2018)
Our density functional theory (DFT)/time-dependent DFT (TDDFT) calculationsfor the sensing mechanism of a series of sulfoxide based metal-responsive fluorescentchemosensors, suggested that the intramolecular charge transfer (ICT) is not areasonable mechanism for these chemosensors. The calculated electronic transition energies,the corresponding oscillator strengths of these chemosensors and the involvingfrontier molecular orbital analysis indicated that there is no obviously ICT state witha transition oscillator strength approaching to zero. The fluorescence quenching ofthese chemosensors cannot be explained by ICT process. The ground state optimizedstructures of chemosensors and their complexes indicated that there might be twistedexcited configuration for these chemosensors and the twisted excited state configurationmay response for the fluorescence quenching. The configuration change can beblocked in the Zn complex that is responsible for these complexes showing fluorescenceemission enhancement. In order to understand the function of the sulfoxidesgroup in these metal-responsive fluorescent chemosensors, excited state configurationoptimization as well as the excited state hydrogen bond effect on the fluorescence enhancementin the aqueous solvent will be conducted.
Keywords: Fluorescent probes; Sensing mechanism; Density functional calculations; Intramolecular charge transfer (ICT); sulfoxide moiety.